2005
DOI: 10.1136/vr.156.17.533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of a synthetic dog‐appeasing pheromone with clomipramine for the treatment of separation‐related disorders in dogs

Abstract: Sixty-seven dogs that showed signs of distress when separated from their owners (destructiveness, excessive vocalisation and house soiling) and hyperattachment were used in a randomised, blind trial to assess the potential value of a dog-appeasing pheromone in reducing the unacceptable behaviours. For ethical reasons, there was no placebo group and the effects of the pheromone were compared with the effects of clomipramine which is regularly used to treat this type of problem. The undesirable behaviours decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 20 publications
3
58
1
4
Order By: Relevance
“…Results of the physiological parameters appear to be consistent with the observations made in various species treated with pheromones belonging to the appeasines range (Gaultier et al, 2005). Indeed, we noticed a stabilization of heart rates, and limitation of the extent of cardiac emotional reaction.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Results of the physiological parameters appear to be consistent with the observations made in various species treated with pheromones belonging to the appeasines range (Gaultier et al, 2005). Indeed, we noticed a stabilization of heart rates, and limitation of the extent of cardiac emotional reaction.…”
Section: Discussionsupporting
confidence: 77%
“…Pheromonotherapy (Pageat, 2001;Pageat and Gaultier, 2003) enables a simplification of treatment for anxiety and phobia related issues in various species (dogs, cats, rabbits, pigs) (Gaultier et al, 2005;Griffith et al, 2000;Mc Glone et al, 1993) but its effectiveness in horses has only been studied in isolated cases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the value of using a synthetic analogue of the dog-appeasing pheromone (DAP) (CEVA Santé Animale) in a variety of fear-inducing circumstances, such as transport (Gaultier and Pageat 2003, Gandia Estellés and Mills 2006), separation from people (Gaultier and others 2005, 2008), firework displays (Sheppard and Mills 2003), attendance at veterinary clinics (Mills and others 2006) and living in a shelter for dogs (Tod and others 2005). In two placebo-controlled studies, in which DAP was used with puppies during an eight-week training programme, Denenberg and others (2005) and Denenberg and Landsberg (2008) observed that puppies without DAP were more distracted and expressed more fear-related signs, such as aggression, avoidance, submissive urination, and fearful postures when facing new circumstances.…”
mentioning
confidence: 99%
“…It can be delivered into the home via a plug-in air diffuser and has been reported to be useful in relieving canine anxiety associated with firework noises (Sheppard and Mills, 2003), travelling (Gandia Estelles and Mills, 2006), being left alone (Gaultier et al, 2005) and within the rescue shelter environment (Tod et al, 2005). In all these situations, tendency to vocalise in particular was reduced.…”
Section: Introductionmentioning
confidence: 99%